Exclusive Breastfeeding Duration and Allergic Asthma Severity in Children - Aida Fahira Rachma; Anang Endaryanto; Deasy Fetarayani; Retno Asih Setyoningrum (Faculty of Medicine Universitas Airlangga, 2021)
Introduction: Asthma is a disease marked by bronchial hyperresponsivity. It is commonly seen in children and often affects their quality of life. Many factors affect asthma, including breastfeeding. Bioactive and immunological components of maternal milk have a protective effect on allergic asthma. However, some studies denied this, stating that it had no significant association to asthma. This study aimed to analyze the correlation between breastfeeding duration and the severity of allergic asthma described by the frequency of asthma attacks, sleep disorder, and activity limitation.Methods: This analytic observational study used a cross sectional approach. The subjects were pediatric outpatients aged 1 – 5 years old with allergic asthma at Pediatric Clinic of Dr. Soetomo General Hospital Surabaya and Private Pediatric Clinic from September 2019 to July 2020. Subjects were assessed based on the history of exclusive breastfeeding duration, frequency of asthma attacks, sleep disorder, and activity limitation through an interview using questionnaire.Results: Through the data obtained from 62 respondents, duration of exclusive breastfeeding showed no significant relation to the frequency of asthma attack (rs = -0.227, p = 0.076), sleep disorder (rs = -0.214, p = 0.095), and activity limitation (rs = -0.055, p = 0.672).Conclusion: There was no correlation between the duration of exclusive breastfeeding and the frequency of asthma attack, sleep disorder, and activity limitation.